Incidente de resolução de demandas repetitivas - Siviero, Flávio Henrique (2022)
This paper analyses the “incidente de resolução de demandas repetitivas” (IRDR) created by the Civil Procedure Code of 2015. In order to reach an appropriate dogmatics for the appreciation of the aforementioned procedural technique, the present academic work makes a brief incursion into the definition of judicial precedent and presents an overview of the other procedural instruments aimed at the creation of mandatory precedent in Brazilian law to then proceed to a in-depth study of the IRDR. In the end, the paper points out the similarities and differences of repetitive demands and homogeneous individual rights, analyzes the constitutionality of the expansion of the competence of the Courts resulting from the creation of an procedural incident that must be originally appreciated by them and seeks to answer the main controversies involving IRDR and small claims courts, notably if an IRDR can be filed before the second-degree body of the small claims courts, if a process in progress in the small claims court can trigger an IRDR and whether it is possible to file a complaint to the Court that judged the IRDR in case of non-compliance with the thesis signed by it in a process that is being processed before the small claims court